BOOK-ALBUM «OLD COURTYARDS AND YARDS OF KRAKOW» («DAWNE DZIEDZIŃCE I PODWÓRZA KRAKOWA») BY LEON GETZ: HISTORY AND ARTISTIC CHARACTERISTICS - Ґах, І. С.; Гаврилюк, Б. А. (Art and Design, 2024)
Purpose: to examine the artistic features of the book-album "Old Courtyards and Alleys of Kraków" (Kraków, 1958) with graphic illustrations by Ukrainian-Polish artist Lev Getz, which is being analyzed as a subject of art historical research for the first time. Methodology. The research employs cultural-historical, structural-typological, formal-descriptive, and systematic analyses. Results. For the first time in Ukrainian art history, this study presents essential information about the book-album "Old Courtyards and Alleys of Kraków", illustrated by the renowned artist Lev Getz. The research briefly describes Getz’s post-war artistic activities in architectural landscape genre and analyzes his series of graphic works dedicated to Kraków’s architecture, which uniquely captures the artistic image of this ancient Polish city. The study notes that Getz portrayed Kraków as a city that preserved its historical area, with distinctive architectural features unique to its character, remarkable monuments, and artistic depth. The artist faithfully depicted both famous city structures and private, less accessible locations – including courtyards and alleys that were either locationally unpopular or unknown to the general public. The research emphasizes the artist’s interest in urban landscape and his ability to capture the essential features of ancient monuments, including their historical, artistic, structural, and decorative motifs. Scientific novelty. This research introduces Lev Getz’s post-war graphics, presented in the book-album "Old Courtyards and Alleys of Kraków", previously unknown in Ukraine, into scholarly discourse. Practical significance. The study not only substantially supplements information about Lev Getz’s artistic legacy but also analyzes architectural landscape in the artist’s creative works from the 1950s-60s. The findings demonstrate the potential for further research into 20th-century fine arts preserved outside Ukraine, as the significance of lesser-known Ukrainian artists’ works continues to grow in today’s turbulent times.